Adjunctive Treatment With Eslicarbazepine Acetate for Adults and Children With Focal-Onset Epilepsy: A Meta-Analysis - Fei, Yanqing; Shi, Ruting; Song, Zhi (Frontiers in Neurology, 2022)
Background: The efficacy and tolerability of eslicarbazepine acetate (ESL) in adults and children with focal-onset epilepsy (FOE) according to the dose remain to be validated. A meta-analysis based on randomized controlled trials (RCTs) was therefore conducted as a summary. Methods: Relevant RCTs were collected by systematic searching the electronic databases of PubMed, Cochrane’s Library, Embase, Wanfang and CNKI from inception to May 16, 2022. The random-effect model was adopted to pool the results by incorporating the possible heterogeneity. Efficacy outcomes including responsive rate and effective rate, defined as cases with 50% and ≥75% reduction in seizure frequency compared to baseline, were determined respectively. Incidence of severe adverse events (AE) leading to drug discontinuation was also evaluated. Results: Ten studies including 2565 people with epilepsy contributed to the meta-analysis. For adults, ESL 400 mg/d did not improve the response rate or the effective rate; ESL 800 mg/d was associated with improved response rate (odds ratio [OR] 2.16, 95% confidence interval [CI]: 1.65-2.83, p<0.001) and effective rate (OR 2.16, 95% CI: 1.41-3.30, p<0.001) without significantly increased severe AE (OR 1.58, 95% CI: 0.90-2.78, p=0.11); ESL 1200 mg/d improved response rate (OR 2.49, p<0.001) and effective rate (OR 3.09, p=0.04), but significantly increased severe AE (OR 3.72, p<0.001). For children, ESL also did not significantly improve the response rate (OR 1.76, p=0.22) or the effective rate (OR 2.17, p=0.13). Conclusion: ESL 800 mg/d is effective and well-tolerated as adjuvants for adults with FOE. Efficacy of ESL in children with FOE should be further evaluated.